The effects of cold, dry and heated, humidified amniotic insufflation on sheep fetal membranes. (October 2021) - Amberg, Benjamin; DeKoninck, Philip; Kashyap, Aidan; Rodgers, Karyn; Zahra, Valarie; Hooper, Stuart; Crossley, Kelly; Hodges, Ryan
Abstract: Introduction: Uterine distension with pressurised carbon dioxide (CO2 ) (amniotic insufflation) is used clinically to improve visibility during keyhole fetal surgery. However, there are concerns that amniotic insufflation with unconditioned (cold, dry) CO2 damages the fetal membranes which leads to post-operative preterm prelabour rupture of membranes (iatrogenic PPROM). We assessed whether heating and humidifying the insufflated CO2 could reduce fetal membrane damage in sheep. Methods: Thirteen pregnant ewes at 103–106 days gestation underwent amniotic insufflation with cold, dry (22 °C, 0–5% humidity, n = 6) or heated, humidified (40 °C, 95–100% humidity, n = 7) CO2 at 15 mmHg for 180 min. Twelve non-insufflated amniotic sacs acted as controls. Fetal membrane sections were collected after insufflation and analysed for molecular and histological markers of cell damage (caspase 3 and high mobility group box 1 [ HMGB1 ]), inflammation (interleukin 1-alpha [ IL1-alpha ], IL8 and vascular cell adhesion molecule [ VCAM ]) and collagen weakening (matrix metalloprotease 9 [ MMP9 ]). Results: Exposure to cold, dry CO2 increased mRNA levels of caspase 3, HMGB1, IL1-alpha, IL8, VCAM and MMP9 and increased amniotic epithelial caspase 3 and HMGB1 cell counts relative to controls. Exposure to heated, humidified CO2 also increased IL8 levels relative to controls however, HMGB1, IL1-alpha and VCAM mRNA levels and amniotic epithelial HMGB1 cell counts were significantly lower than the cold, dry group. Discussion: Amniotic insufflation with cold, dry CO2 damaged the amniotic epithelium and induced fetal membrane inflammation. Heated, humidified insufflation partially mitigated this damage and inflammation in sheep and may prove an important step in reducing the risk of iatrogenic PPROM following keyhole fetal surgery. Highlights: Amniotic insufflation with CO2 gas improves visibility during keyhole fetal surgery. Preterm fetal membrane rupture is a common complication of these surgeries. Using unconditioned CO2 for amniotic insufflation damages the fetal membranes. Heated, humidified amniotic insufflation protects the fetal membranes from damage.